Hādī al-‘Alawī and the Heterodoxy of Communo-Sufism - Abdul Kadir Riyadi (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2020)
Sufism is frequently associated with heresy, which is partly due to a controversial thought by a man called Hādī al-‘Alawī, the major concern of this paper. By using the concept of heterodoxy, this study attempts to access the matrix of tensions and representations inherent within his so-called Communo-Sufism. It showed that as a communist, the scholar viewed traditional Islam as a feudalized form of religion in the first phase of his life. This was a kind of natural betrayal to the genuine religiosity and spirituality represented by what al-‘Alawī called the “Jahili-Islam.” According to this individual, the Jahili-Islam was authentic, and Muhammad’s version of it was a sheer distortion of true Islam. Also, the paper revealed that as a communist-Sufi, this theorist proposed a distinction between the “dead Islam” and “living Islam” in the second phase of his life. The former was represented by traditional Muslim faithful adhering to Muhammad’s version of the religion while the latter was the continuation of the Jahili-Islam. Based on al-‘Alawī’s discourse, this religion can only live on if it is based socially and legally on the Jahili-Islam. Theologically, Islam must be based on the Judeo-Christian traditions, philosophically on the Persian and Byzantine episteme, ideologically on Communism, and spiritually on Sufism. Although these premises seem vibrant at the surface, they are nonetheless anarchistic and are an antithesis to the existing paradigmatic form of Islam.